PENGARUH PROFITABILITAS DAN STRUKTUR MODAL TERHADAP NILAI PERUSAHAAN DENGAN KEBIJAKAN DIVIDEN SEBAGAI VARIABEL MODERASI PADA PERUSAHAAN BANK KONVENSIONAL YANG TERDAFTAR DI BEI PERIODE 2020-2023 - Chofifa, Siti; Subaida, Ida; Widaninggar, Nanda (Jurnal Mahasiswa Entrepreneurship (JME), 2025)
Effective financial management is crucial for a company’s financial system to ensure smooth operations and achieve its objectives. Therefore, Profitability, Capital Structure, and Dividend Policy variables are important because they can influence a company’s performance and financial performance. This study used conventional banks listed on the Indonesia Stock Exchange from 2020 to 2023. The researcher chose Conventional Banks as the research subjects because these banks demonstrated significant resilience during the COVID-19 pandemic, remaining able to channel funds to the public and maintain stable performance despite declining credit demand due to sluggish economic activity. This study aims to analyze and test the moderating effect of Dividend Policy on Firm Value. The population in this study was 47 conventional banks listed on the Indonesian Stock Exchange during the study period. The sampling technique was purposive sampling. Data analysis and hypothesis testing used Partial Least Squares-Structural Equation Modeling (PLS-SEM). The results of the hypothesis test using the Smart PLS 3.0 application indicate that profitability has a positive and significant effect on firm value, capital structure has a positive but insignificant effect on firm value, dividend policy has a negative but insignificant effect in moderating the effect of profitability on firm value, and dividend policy has a positive but insignificant effect in moderating the effect of capital structure on firm value.